Pengaruh Model Pembelajaran Cooperative Learning terhadap Hasil Belajar Matematika Siswa Kelas IV Materi Pecahan di SDN 104204 Sambirejo Timur T.A 2022/2023 - Lisa Anggia Lubis; Ibrahim Gultom (Journal on Education, 2023)
This study aims to determine the effect of the jigsaw type cooperative learning model and the prediction guide cooperative learning type and to find out whether there is a higher effect of the jigsaw type cooperative learning model and the prediction guide cooperative learning type on the mathematics learning outcomes of fourth grade students on fraction material at SDN 104204 East Sambirejo Academic Year 2022/2023. This type of research uses a quantitative approach using a quasy experimental design. The research sample consisted of 47 students with 26 students from class IV A and 21 students from class IV B. Class IV A as the experimental class used the jigsaw cooperative learning model and class IV B as the experimental class used the cooperative learning model of the prediction guide type. . This research data collection technique is in the form of a test. The pre-test average score in class IV A was 67.42 and the post-test score was 87.55 whereas, for class IV B the pre-test average score in class IV A was 49.57 and the post-test score was 66,66. Based on the results of the t-test above, the Sig (2-tailed) value was obtained at 0.000 <0.05. It can be concluded that the learning outcomes of students using the jigsaw cooperative learning model are higher or superior than using the prediction guide cooperative learning model in class IV SDN 104204 Sambirejo Timur T.A 2022/2023